Synthesis, crystal structure study and high efficient catalytic activity of di-μbromo-trans–dibromobis[(benzyl)(4-methylphenyl)(phenyl)phosphine] dipalladium(II) in Suzuki–Miyaura and Heck–Mizoroki C–C coupling reactions. (24th November 2016) - Ghorbani-Choghamarani, Arash; Naghipour, Ali; Babaee, Heshmatollah; Notash, Behrouz
Graphical Abstract: In this research article di-μbromo-trans–di bromobis(benzylphenylparatulylphosphine) dipalladium(II) has been prepared and characterized by X-Ray crystallography. This compound has been applied as catalyst for the C-C cross-coupling reactions. Abstract: The current research aims to present a straightforward synthesis of binuclear palladated triphenylphosphine derivative by the reaction of the phosphonium salt [(PhCH2 )P(Ph)2 (Ph-4-CH3 )]Br with palladium(II) chloride and to afford the dimeric palladated complex Pd[P(Ph)(CH2 Ph)(Ph-4-CH3 )]((μ-Br)Br)2 . Moreover, elemental analysis (CHN), FT-IR, 1H, 31P, 13C NMR and X-ray crystallography led to the characterization of the obtained compound. Finally, This compound was found to be an efficient catalyst in C–C bond formation between various aryl halides with phenylboronic acid (Suzuki–Miyaura reaction) and aryl halides with n -butyl acrylate (Heck–Mizoroki reaction).